The Near Point of Convergence in Patients with Vestibular Migraine - Francisco Carlos Zuma e Maia; Bernardo Faria Ramos; Roseli Saraiva Moreira Bittar; Renato Valerio Rodrigues Cal; Leonel Almeida Luís; Pedro Luiz Mangabeira Albernaz (International Archives of Otorhinolaryngology)
Introduction Vestibular migraine (VM) is one of the most common vestibular disorders and its diagnosis is based entirely on clinical features. A recent case series suggested a possible link between migraines and convergence insufficiency.